Fulfillment Consumers’ Right to Departure Information During Flight Delays: A Case Study of Airline Passengers in Indonesia - Evi Marpaung (Universitas Negeri Semarang, 2026)
This study aims to analyze the fulfillment of consumers’ rights to departure information in the event of flight delays and to examine the extent of airlines’ liability for the resulting uncertainty in information. The method used is a normative legal approach with a legislative and conceptual perspective, supported by a case study of passengers on a Jakarta–Surabaya flight that experienced a delay of more than four hours accompanied by unclear and inconsistent information. The research findings indicate that the right to information, as a fundamental consumer right, has not been optimally fulfilled, marked by a lack of clarity regarding the causes of delays, inconsistencies in information, and delays in conveying information to passengers. Furthermore, the services and compensation provided by the airline do not fully reflect the principles of proportionality and fairness. From a civil law perspective, this situation can be classified as a breach of contract in the form of imperfect performance (onvolledige nakoming), as the airline’s obligations extend beyond merely transporting passengers to include informational obligations as part of the contractual performance. Therefore, improved transparency, consistent communication, and more effective oversight are necessary to ensure the fulfillment of consumer rights in the air transport sector